Clinical and pathological characterization of FLNC‐related myofibrillar myopathy caused by founder variant c.8129G>A in Hong Kong Chinese. Issue 5 (23rd February 2020) - Lee, Han‐Chih Hencher; Wong, Shun; Sheng, Bun; Pan, Nin‐Yuan Keith; Leung, Ying‐Kit Frank; Lau, Kwok‐Kwong Dominic; Cheng, Yue Sandy; Ho, Luen‐Cheung; Li, Richard; Lee, Chi‐Nam; Tsoi, Tak‐Hong; Cheung, Yuk‐Fai Nelson; et al.
Abstract: FLNC ‐related myofibrillar myopathy could manifest as autosomal dominant late‐onset slowly progressive proximal muscle weakness; involvements of cardiac and/or respiratory functions are common. We describe 34 patients in nine families of FLNC ‐related myofibrillar myopathy in Hong Kong ethnic Chinese diagnosed over the last 12 years, in whom the same pathogenic variant c.8129G>A (p.Trp2710*) was detected. Twenty‐six patients were symptomatic when diagnosed; four patients died of pneumonia and/or respiratory failure. Abnormal amorphous material or granulofilamentous masses were detected in half of the cases, with mitochondrial abnormalities noted in two‐thirds. We also show by haplotype analysis the founder effect associated with this Hong Kong variant, which might have occurred 42 to 71 generations ago or around Tang and Song dynasties, and underlain a higher incidence of myofibrillar myopathy among Hong Kong Chinese. The late‐onset nature and slowly progressive course of the highly penetrant condition could have significant impact on the family members, and an early diagnosis could benefit the whole family. Considering another neighboring founder variant in FLNC in German patients, we advocate development of specific therapies such as chaperone‐based or antisense oligonucleotide strategies for this particular type of myopathy. Abstract : FLNC‐related myofibrillar myopathycould manifest as autosomal dominant late‐onset slowly progressive proximal muscle weakness; involvements of cardiac and/or respiratory functions are common. We describe 34 patients in nine families of FLNC‐related myofibrillar myopathy in Hong Kong ethnic Chinese diagnosed over the last 12 years, in whom the same pathogenic variant c.8129G>A (p.Trp2710*) was detected. Abnormal amorphous material or granulofilamentous masses were detected in half of the cases, with mitochondrial abnormalities noted in two thirds. We also demonstrate by haplotype analysis the founder effect associated with this Hong Kong variant.